2020
DOI: 10.3390/nu12061632
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Bone Microarchitecture in a Cohort of Systemic Sclerosis Patients

Abstract: Systemic sclerosis (SSc) is a connective tissue disease characterized by initial microvascular damage, immune system activation and progressive fibrosis with insufficiency of internal organs. Gastrointestinal (GI) involvement is characterized by atrophy of the smooth muscle and small bowel hypomotility, mainly resulting from an autonomic nerve dysfunction. These modifications significantly affect gut transit and nutrient absorption, thus leading to malnutrition deficit induced by malabsorption. Nutritional def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…Some studies have focused on statistically significant relationships between vitamin D and parathyroid hormone (PTH), not only in healthy individuals but also in SSc patients [ 12 , 13 , 31 , 35 , 46 ]. Furthermore, Hax et al demonstrated that 25-hydroxyvitamin D [25(OH)D] levels are inversely correlated with PTH [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have focused on statistically significant relationships between vitamin D and parathyroid hormone (PTH), not only in healthy individuals but also in SSc patients [ 12 , 13 , 31 , 35 , 46 ]. Furthermore, Hax et al demonstrated that 25-hydroxyvitamin D [25(OH)D] levels are inversely correlated with PTH [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hax et al demonstrated that 25-hydroxyvitamin D [25(OH)D] levels are inversely correlated with PTH [ 12 ]. Paolino et al identified significant differences in malnourished SSc patients in the median values of PTH and vitamin D levels [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes could be associated with less epigastric pain. However, this could have contributed to the reduction the symptoms even in the NCS-f diet group because suboptimal body composition is associated with more gastrointestinal symptoms [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A further study by Paolino et al investigated the impact of gastrointestinal (GI) involvement on bone microarchitecture in systemic sclerosis (SSc). GI involvement in SSc is characterised by the atrophy of the smooth muscle and small bowel hypomotility, overall coming from autonomic nerve dysfunction [9]. These alterations significantly affect gut transit and nutrient absorption, culminating in nutritional deficits induced by malabsorption that consequently also led to bone alterations.…”
mentioning
confidence: 99%